1986
DOI: 10.1266/jjg.61.515
|View full text |Cite
|
Sign up to set email alerts
|

New shuttle vectors for Escherichia coli and Bacillus subtilis. IV The nucleotide sequence of pHY300PLK and some properties in relation to transformation.

Abstract: The whole nucleotide sequence of pHY300PLK (Ishiwa and Shibahara 1985a) has been determined, pHY300PLK consists of 4870 by and contains an RNA primer for on-177 and three open reading frames corresponding to TcR, ApR and Rep-al. Twenty-three unique restriction endonuclease recognition sites were found. We have confirmed that ORF al of pHY300PLK is the plasmid replication gene. A rescue phenomenon has been found with respect to multiple infection by pHY300.2PLK (rep-) and pUB110. A series of experiments indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 22 publications
0
42
0
Order By: Relevance
“…The wprA plasmid was digested with BglII, which cut the wprA-coding region in the middle. A 1.5-kb fragment of the tetracycline-resistance gene (tetL) of plasmid pHY300PLK 24) was amplified with primer pair tetL-F1/tetL-B1 (Table 2), trimmed with BglII, and ligated to the BglII arms of the wprA plasmid. A 5.5-kb DNA fragment was amplified by PCR with primer pair wprA-F/wprA-B, and was subjected to transformation of r22 to tetracycline resistance (10 mg/mL).…”
Section: Methodsmentioning
confidence: 99%
“…The wprA plasmid was digested with BglII, which cut the wprA-coding region in the middle. A 1.5-kb fragment of the tetracycline-resistance gene (tetL) of plasmid pHY300PLK 24) was amplified with primer pair tetL-F1/tetL-B1 (Table 2), trimmed with BglII, and ligated to the BglII arms of the wprA plasmid. A 5.5-kb DNA fragment was amplified by PCR with primer pair wprA-F/wprA-B, and was subjected to transformation of r22 to tetracycline resistance (10 mg/mL).…”
Section: Methodsmentioning
confidence: 99%
“…Plasmid pUC19 20) and pE194 21) were from our laboratory stock. pHY300PLK 22,23) was purchased from Takara Shuzo Co., Ltd. (Kyoto, Japan). In order to remove an unnecessary region from pHY300PLK, oripACYC177 and Ap r gene were cut out by digestion with AccI, and self-ligated with T4 DNA ligase.…”
Section: Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
“…Subcloning showed that a 3.1-kb SspI-SspJ region of the insert contained the region essential for the EG activity. The SspI-SspI fragment was inserted into the SmaI site of plasmid pHY300PLK 19) and the resultant recombinant plasmid was designated pBEG38 (8.0 kb). pBEG38 was then expressed both in E. coli and in B. subtilis and EG-positive transformants were detected by the Congo red-CMC procedure.…”
Section: Methodsmentioning
confidence: 99%